Bireysel iş uyuşmazlıkları bakımından dava şartı arabuluculukta taraflar - Güngör, Tuba (Kırıkkale Üniversitesi, 2024)
Türk hukukunda, özellikle iş uyuşmazlıkları bakımından arabuluculuğun dava şartı olarak kabul edildiği tarihten bu yana, arabuluculuk kurumundan beklenen faydanın elde edilip edilmediği bir yana bırakılırsa öğreti ve uygulamada halen tartışıla gelen birçok konu bulunmaktadır. Bunlardan biri, çalışma konumuzu oluşturan bireysel iş uyuşmazlıkları bakımından dava şartı arabuluculukta işçi ve işveren tarafların doğru ve tam olarak teşkilinin sağlanmasıdır. Alternatif çözüm yollarından biri olan arabuluculuğun dava şartı olarak düzenlenmesi, arabuluculuk faaliyetini yargılamanın ön şartı ve ayrılmaz bir parçası haline getirmiştir. Bu bakımdan arabuluculuk sürecinin doğru işçi veya işveren tarafla yürütülmemesi yargılamayı doğrudan etkileyecektir. İş uyuşmazlıkları bakımından işçi sıfatının belirlenmesi özellikle işçi olup olmadığı konusunda tereddüt yaşanan çalışanlar açısından önemlidir. İşveren tarafının doğru belirlenmesi ise, arabuluculuk faaliyetinin yanlış veya eksik işverenle yürütülmesinin ardından, yargılama sürecinde bu durumun tespit edilmesi halinde işveren tarafında değişiklik yapılamaması bakımından önem arz etmektedir. Arabuluculuk dava şartı olarak düzenlendiğinden, yargılama sırasında tamamlanabilmesi olanaklı değildir. Sürecin bu şekilde işlemesi ise mahkemeye erişim hakkının önünde engel teşkil edebileceği gibi, gerek iş güvencesi gerekse işçinin alacağına kavuşma noktasında hak kaybına ve mağduriyetine yol açabilecektir. In Turkish law, especially since the adoption of mediation as a condition for litigation in terms of labour disputes, there are still many issues that are still debated in the doctrine and practice, let alone whether the expected benefit of the mediation institution has been achieved. One of these issues is to ensure that the employee and employer parties are accurately and fully constituted in the mediation as a condition for litigation in terms of individual labour disputes, which is the subject of our study. The regulation of mediation as a condition of litigation, which is one of the alternative remedies, has made the mediation activity a prerequisite and an integral part of the proceedings. In this respect, failure to conduct the mediation process with the right employee or employer party will directly affect the proceedings. In terms of labour disputes, the determination of the employee party is especially important for employees who are in doubt as to whether they are employees or not. The correct determination of the employer party is important in terms of not being able to make changes on the employer side if this situation is detected during the proceedings after the mediation is carried out with the wrong or incomplete employer. Since mediation is regulated as a condition of litigation, it is not possible to complete it during the proceedings. This process may constitute an obstacle to the right of access to the court, and may lead to loss of rights and victimisation in terms of both job security and the employee's receivables.
Keywords: Dava şartı arabuluculuk; Employee; Employer; Iş uyuşmazlığı; Işveren; Labour dispute; Mediation; İşçi

Arabuluculuk faaliyetinin anlaşma ile sona ermesi - Terzi̇ Kahraman, Si̇bel (Kadir Has Üniversitesi, 2024)
Arabuluculuk kurumundan beklenen avantajların ortaya çıkabilmesi arabuluculuk faaliyeti sonunda anlaşmaya varılması ile mümkündür. Mevzuatta sürekli değişiklikler meydana gelmekte ve kurumun kapsamına aldığı uyuşmazlıklar hızla genişletmektedir. Uygulamanın yerleşmesi ve zaman zaman doktrinde görüş ayrılıkları yaşanması kaçınılmazdır. Mevzuatta daha detaylı ya da değiştirilerek düzenlenmesine ihtiyaç duyulan alanlar bulunmaktadır. Tez, mevzuatta yapılan son düzenlemeleri de kapsayarak anlaşmayı tüm yönleriyle ele almayı ve kurumun daha iyi anlaşılmasına hizmet etmeyi amaçlamaktadır. Yapılan bu çalışmanın ilk bölümde arabuluculuğun kurumsal çerçevesi ortaya konulmuştur. Bu bölümde amaç arabuluculuk kurumunu ve arabuluculuk faaliyetinin işleyişini anlatabilmektir. Bu amaçla arabuluculuğun kapsamı, türleri, arabuluculuğun karşılaştırmalı hukukta ve Türk hukukunda gelişimi, yargı ve tahkimden farkı, med-arb uygulaması anlatılmıştır. İkinci bölümde sona erme halleri tek tek ele alınmış, sona erme hallerinin mevzuatta dağınık halde düzenlendiği hususuna dikkat çekilmiş ve başkaca sona erme halleri de dikkate alınarak tek bir madde halinde düzenlenebilmesi hususu önerilmiştir. Arabulucunun, faaliyeti sona erdirme yönünde inisiyatif almasının sona erme hali olarak düzenlenmesi yönünde de öneri getirilmiştir. Üçüncü bölümde anlaşmanın terminoloji sorununa ve benzer kavramlardan farkına değinilmiştir. Arabuluculuk faaliyeti sonunda varılan anlaşmanın esaslı unsurları tespit edilmiştir. Bu kapsamda, sözleşme serbestisi, şarta bağlı edim düzenlenip düzenlenemeyeceği gibi önemli hususlara yer verilmiştir. Anlaşmanın nasıl düzenleneceğine ilişkin öneride bulunulmuştur. Anlaşmanın hukuki niteliği, anlaşılan hususlara karşı dava açılamayacağı, anlaşmanın hukuka uygun düzenlenmediği takdirde karşılaşılabilecek sonuçlar anlatılmış ve anlaşmanın arabuluculuğa elverişli olmamasına rağmen düzenlenmesi, dava şartı kapsamına girmeyen bir hususta faaliyetin yürütülmesi ve anlaşmaya varılması, yanlış dava türünden yapılan başvuru sonucu anlaşmaya varılması, arabulucunun uzmanlık alanına girmeyen bir konuyla ilgili anlaşma sürecini tamamlaması, hukuka uygun arabuluculuk faaliyeti yürütülmemesi sonucunda anlaşmaya varılması, arabulucunun arabuluculuktan çekilmesi gerekirken yine de anlaşma yapması gibi anlaşmadan kaynaklı sorunlara yer verilmiştir. Dördüncü bölümde anlaşmanın yerine getirilmemesi durumunda icra edilebilirlik şerhi alınması hususu, mahkemeye başvuru, yargılama usulü, mahkemenin incelemesi, şarta bağlı olarak yapılan anlaşmaya şerh verilmesi, icra edilebilirlik şerhi alınan anlaşmanın icrası, anlaşmayla ilamlı ve ilamsız takip yapılması gibi önemli hususlar ele alınmıştır. Son olarak, arabuluculuk sonucunda elde edilen uluslararası ticari anlaşmaların icra edilmesini kolaylaştırması amacıyla hukukumuzda da kabul edilen Singapur Konvansiyonu incelenmiştir. The expected advantages of the mediation institution can be realized through reaching an agreement at the end of the mediation process. There are continuous changes in the legislation, rapidly expanding the scope of disputes covered by the institution. The thesis aims to comprehensively examine the agreement reached at the end of the mediation process, including recent legislative amendments, to better understand the institution and its operations. The first part of this study outlines the institutional framework of mediation, explaining its scope, types, development in comparative law and Turkish law, differences from judiciary and arbitration, and the practice of med-arb. The second part discusses the various termination conditions, highlighting the scattered nature of these conditions in legislation and proposing their consolidation into a single provision. It also suggests granting mediators the initiative to terminate the process as a termination condition. In the third part, attention is given to the terminology issues and distinctions from similar concepts regarding the agreement reached through mediation. The essential elements of such agreements are identified, covering issues like contractual freedom and the regulation of conditional obligations. Recommendations are made on how agreements should be drafted. The legal nature of the agreement, restrictions on litigation concerning agreed-upon matters, consequences of improperly drafted agreements, and issues arising from inappropriate mediation activities are discussed. The fourth part addresses the issue of obtaining enforceability endorsements for agreements not fulfilled, court applications, trial procedures, court reviews, endorsement of conditional agreements, enforcement of endorsed agreements, and procedures for enforcement with and without judgments. Finally, the study explores the Singapore Convention, adopted in our legal system to facilitate the enforcement of international commercial agreements resulting from mediation.
Keywords: ADR; Agreement termination; Alternative dispute resolution; Anlaşmazlık; Arabuluculuk; Executability Annotation; Kanunlar 6325 sayılı; Laws 6325 numbered; Mandatory mediation; Mediation; Mediator; Médiation; Singapore Convention; Zorunlu arabuluculuk

Sermaye şirketlerinde zorunlu arabuluculuk - Ulusan, Banu (Galatasaray Üniversitesi, 2024)
Çalışma 06.12.2018 tarihinde 7155 sayılı Kanun ile Türk Ticaret Kanunu'na eklenen TTK m. 5A hükmüyle getirilmiş zorunlu arabuluculuğun, sermaye şirketleri çerçevesinde incelenmesini konu almaktadır. TTK m. 5A hükmüyle önce, ticari davalardan, konusu bir miktar paranın ödenmesi olan, alacak ve tazminat davalarının zorunlu arabuluculuğa tabi olduğu düzenlenmiştir. Daha sonra, 28.02.2023 tarihli ve 7445 sayılı Kanun ile yine ticari dava olmaları kaydıyla, menfi tespit, itirazın iptâlî ve istirdat davalarını da zorunlu arabuluculuk kapsamına almıştır. TTK lafzıyla dava şartı arabuluculuk olarak da nitelendirilen zorunlu arabuluculuk kavramı, Türk hukuku bakımından yeni bir kavram sayılabilir. İlk olarak 2017 yılında 7036 sayılı Kanun ile iş uyuşmazlıkları için düzenlenen zorunlu arabuluculuk kavramı, daha sonra ticari uyuşmazlıklar ve tüketici uyuşmazlıkları için de düzenlenmiştir ve Türk hukukunda zorunlu arabuluculuğun uygulama alanı git gide genişleme eğilimi göstermektedir. Bu sebeple, doktrinde pek çok eleştiriye de uğrayan zorunlu arabuluculuk kavramının, özellikle sermaye şirketleri bağlamında incelenmesi amaçlanmıştır. Her ne kadar Türk hukukunda yeni bir kavram olsa da, karşılaştırmalı hukukta zorunlu arabuluculuk uzun zamandan beri uygulanan ve tartışilânbir konu olagelmiştir. Karşılaştırmalı hukuk bağlamında bir inceleme yapıldığında öncelikle, özellikle zorunlu arabuluculuğun menşei sayılabilecek Amerikan hukukunda, konu özellikle doktrinde farklı açılardan ele alınmıştır. Çalışmanın birinci bölümünde bu çerçevede bir inceleme yapılmış, zorunlu arabuluculuğun tabi olması gereken kıstaslar ortaya konulmaya çalışılmıştır. Bu kıstaslar, çalışmanın ilerleyen bölümlerinde yapılacak değerlendirmeler için de önem taşımaktadır. Bunun yanı sıra zorunlu arabuluculuğun türleri ve zorunlu arabuluculuğa aykırı davranışlara bağlanan yaptırımlar üzerinde de durulmuştur. Zorunlu arabuluculuğun ve benzeri uygulamaların farklı hukuk sistemlerinde ne şekilde yer aldığı değerlendirilmiştir. Bu değerlendirmeler kapsamında Alman hukuku bakımından ZPO §278 ile EGZPO §15a incelenmiştir. İsviçre hukuku bakımından ise ZPO §197 vd. hükümleri incelenmiştir. Her iki hukuk sistemi de zorunlu arabuluculuğu düzenlememiş, bunun yerine medeni usûl kanunlarında davanın görüleceği mahkemeler nezdinde uyuşmazlık çözüm sürecini düzenlemiştir. İtalya ve Fransa'da ise zorunlu arabuluculuk uygulamaları mevcut ise de bu, Türk hukukunun aksine, son derece sınırlı bir şekilde gerçekleşmiştir. Zorunlu arabuluculuğun kaynağı olan Amerikan hukukunda ise arabuluculuk, zorunlu tutulan tek uyuşmazlık çözüm yöntemi olmamıştır. Ayrıca zorunluluk hususu kanunla değil, genellikle her bir dava için mahkemenin yönlendirmesiyle sağlanmaktadır. Tüm bu ülkelerin ortak özelliği ise ticari uyuşmazlıkları zorunlu arabuluculuğa ya hiç tabi tutmamaları ya da çok dar bir kapsamda tabi tutmalarıdır. Arabuluculuk her ne kadar bir yargılama faaliyeti olmasa da zorunlu arabuluculuk dava öncesinde yer alan bir aşama olduğundan, kanaatimizce medeni usûl hukukuna hâkim olan ilkeler bakımından da incelenmelidir. Bu kapsamda zorunlu arabuluculuğun öncelikle adil yargılanma ilkesi ve mahkemeye erişim hakkı kapsamında tartışmalara sebep olduğu görülmektedir. Bunun yanı sıra usûl ekonomisi ilkesi, aleniyet ilkesi, tasarruf ilkesi ve dürüst davranma yükümlülüğü bakımından da değerlendirmelere yer verilmiştir. Aleniyet ilkesi bağlamında arabuluculuğa hâkim olan ilkelerden gizlilik ilkesinin ticari uyuşmazlıklar bakımından bir avantaj oluşturduğu söylenebilir. Tasarruf ilkesinde yapılandeğerlendirme maddî hukuk ve usûl hukuku çerçevelerinde yapılmıştır. Ayrıca zorunlu arabuluculuğun menşei Amerikan hukukunda hâkimin ve avukatların rolleri de dikkate alınarak, zorunlu arabuluculuğun Türk hukukundaki hâkimin yargılamayı sevk ve idaresi ilkesiyle tamamen bağdaşmadığı sonucuna varılmıştır. Dürüstlük ilkesi bakımından yine maddî hukukla da bağlantı kurularak bir değerlendirme yapılmış, zorunlu arabuluculuk süreci sonunda varılacak anlaşmanın dürüstlük kuralına uygun yapılması için yeterli mekanizmaların bulunmadığı kanaatine varılmıştır. Bunun dışında HUAK m. 18A/11 hükmü uyarınca zorunlu arabuluculuk sürecinin ilk toplantısına mazeretsiz katılmayan tarafın her durumda yargılama giderlerinin tümünden sorumlu olması ve lehine vekalet ücretine hükmedilememesinin orantısız bir yaptırım olduğu, ayrıca bu sebeple hiçbir durumda yargılama giderlerinden sorumlu olmayacağını bilen tarafın, açılacak dava sürecinde davayı uzatacak veya yanlış yönlendirecek ve dürüstlük kuralına uymayacak her tür davranışı yapabileceği kanaatine varılmıştır. Çalışmanın ikinci bölümü TTK m. 5A hükmünün uygulama koşullarına yoğunlaşmaktadır. Bu kapsamda, ticari davalar bakımından karşılaştırmalı bir değerlendirme yapılmak istenmiştir. Türk hukukunda TTK m. 4 hükmüyle ayrıca düzenlenen ticari davalar, diğer hukuk sistemlerinde ticaret mahkemeleriyle ilişkili olarak düzenlenmiştir. Bu değerlendirmede dikkat çeken husus, davaların ucuz, hızlı ve etkin bir şekilde sonuçlandırılmasının amaçlandığı diğer hukuk sistemlerinde hukukçu olmayan hâkimlerin de görev yaptığıdır. Türk doktrininde ise böyle bir uygulamanın uygun olmayacağı haklı olarak belirtilmiş, bu bağlamda zorunlu arabuluculuk uygulamasının daha uygun olduğu kanaatine varılmıştır. Ticari davalarda dava şartını düzenleyen TTK m. 5A hem medeni usûl hukuku hem de ticaret hukuku bakımından incelenmiştir. Medeni usûl hukukun bakımından yapılanincelemede dava şartı kavramı ve hükmün dava türlerine göre gösterdiği özellikler incelenmiştir. Ticaret hukuku bakımından ise, arabuluculuk süreci sonucunda varılacak anlaşmanın bir maddî hukuk sözleşmesi oluşundan da yola çıkarak basiretli tacir kavramı incelenmiştir. Ayrıca zorunlu arabuluculuğun HUAK m. 5 hükmü ve gizlilik ilkesi nedeniyle göstereceği özellikler nedeniyle, ticari sırların korunması bağlamında da bir değerlendirme yapılmıştır. Çalışmanın üçüncü ve son kısmı sermaye şirketlerinde zorunlu arabuluculuğun incelenmesine ayrılmıştır. Bunun için öncelikle Alman hukukunda pay sahipleri davaları olarak adlandırilândavalar hakkında değerlendirme yapılmaya çalışılmıştır. Bu değerlendirmeyle adi şirketlerden farklı olarak pay sahipleri davalarının genel olarak ortağa değil şirket tüzel kişiliğine yöneltilmesi gerektiği, bunun yanı sıra pay sahiplerinin şirketin menfaatleri için dava haklarını kullanabildiği görülmüştür. Bu değerlendirmenin, sermaye şirketleri uyuşmazlıklarında zorunlu arabuluculuk sürecinde başvuru yapacak taraflar ve anlaşmanın etkileyeceği kişilerin tespitinde yararlı olduğu kanaatindeyiz. Bu değerlendirmenin ardından TTK m. 5A kapsamına girebilecek sermaye şirketi uyuşmazlıkları tespit edilerek, her biri için zorunlu arabuluculuğun göstereceği özelliklerin belirlenmesine çalışılmıştır. Bu belirleme yapılırken her bir uyuşmazlık konusu hakkında genel bir çerçeve sunulmuş, açılabilecek davalar hakkında bilgi verilmiş ve bu bilgiler ışığında zorunlu arabuluculuğun uygulama koşulları ile doğurabileceği sakıncalar üzerinde durulmuştur. Son olarak, yapılantüm değerlendirmeler ışığında sermaye şirketlerinde zorunlu arabuluculukla ilgili de lege ferenda görüşümüze yer verilmiştir. Bu kapsamda sermaye şirketleri uyuşmazlıklarının, dava konularının şirketler hukuku kısıtlarına ve emredici kurallara tabi olması sebebiyle, zorunlu arabuluculuğa her zaman uyumlu olmayabileceği sonucuna varılmıştır. Üstelik, bazı arabuluculuk türlerinde yapılması elzem hukuki denetimin ve arabulucunun bu denetimi yapamayacak olmasının yaratacağı sakıncalara da değinilmiştir. Bunun sonucunda İsviçre ve Almanya örneklerinde olduğu gibi mahkeme bağlantılı uyuşmazlık çözümlerinin düzenlenmesinin daha uygun olduğu kanaatine varılmıştır. İflas bakımından bir değerlendirme yapıldığında ise, İİK m. 226 hükmü nedeniyle doğabilecek sorunlara dikkat çekilmiş, bu bağlamda zorunlu arabuluculuğa başvuru kapsamında düzenleme yapılması önerilmiştir. Son olarak zorunlu arabuluculuk ile varılmak istenen amaçlar da dikkate alındığında, bu amaçlara ulaşmak için taraflara arabuluculuk dışında uyuşmazlık çözüm yollarına başvurabilmelerine imkân verilmesi gerektiği kanaatine varılmıştır. Bu şekilde hem çabuk ve ucuz bir şekilde uyuşmazlıkların çözümü amacına ulaşabilecek, hem de tarafların ihtiyaçlarına daha uygun bir yöntem seçmelerine imkân tanınacaktır. […] This study focuses on application of Turkish Commercial Code Art. 5A, which is amended with Code Nr. 7155 in 2018, to equity companies. TCC Art. 5A regulated mandatory mediation for commercial cases with monetary claims at the beginning. However, through amendment with Code Nr. 7445 in 2023, negative declaratory actions, actions for annulment of objections and actions for restitution were taken into scope of this regulation. Mandatory mediation, which can also be named mediation as cause of action according to TCC m. 5A, can be deemed as a new context in Turkish law. Regulated for the first time for some labour law conflicts with Code Nr. 7036 in 2017, mandatory mediation is regulated also for commercial conflicts as well as consumer law conflicts. Thus, it can be observed that scope of mandatory mediation in Turkish law has a tendency to spread within time. Therefore, as a concept subject to various critics, mandatory mediation is to be evaluated in context of equity companies within this study. Although mandatory mediation is considered to be a relatively new concept in Turkish law, in frame of comparative law, it has a long history of application and has been subject to critics for a long time. It is observed that in comparative law, especially in American law, which can be considered as the source, mandatory mediation has been taken into consideration with many aspects. The first chapter of this study conducts an evaluation within this frame and aims to set the criterias for a better application of mandatory mediation. These criterias are important for evaluation in following chapters of this study. In addition, the variations of mandatory mediations and sanctions applied to the acts contrary to mandatory mediations are observed. Mandatory mediation and similar applications in different law systems are also examined. Within light of this examination, ZPO §278 and EGZPO §15a in German law is taken into consideration, as well as ZPO §197 ff. in Swiss law. Both systems do not regulate mandatory mediation and instead, regulated dispute resolution process within their Civil Procedure Codes. Although mandatory mediation is regulated in Itâlîan and French law systems, these regulations have strictly limited scope. American law, the origin of mandatory mediation, applies other means of dispute resolution as well. Moreover, mandatory mediation in American law is not regulated by a code; it is court oriented in general. The common point of these countries is that none of them applies mandatory mediation within a wide scope on commercial disputes. Although mediation cannot be considered as an act of judication, since mandatory mediation is a step before courts, it should be evaluated with regard of principals of civil procedure law. In this context, it is observed that mandatory mediation gave reason to many arguments related to fair trial and access to court. In addition, evaluations on principals pf procedural economy, publicity, power of disposition and honesty are conducted. With regard of principal of publicity, it can be considered that principal of confidentiality of mediation is an advantage. The evaluations on principal of power of disposition are made in frame of substantial and procedural law. Furthermore, taking the features of American civil procedure law, it is concluded that mandatory mediation is not compatible with the role of judge in Turkish law. With regard of principal of honesty, an evaluation in the light of substantial law is also made and it is concluded that rules to maintain honesty in mandatory mediation are not sufficient in Turkish law. As an addition, it is also stated that sanction in Code of Mediation Art. 18A/11 is unproportionate in context of principal of honesty before courts. The second chapter of this study focuses on conditions of TCC Art. 5A. With this regard, a comparative evaluation on commercial actions is made. Commercial actions, regulated with TCC Art. 4 in Turkish law, are regulated in relation with commercial courts in other law systems. With this evaluation, it is noted that in commercial courts, which aims to solve disputes in a cheap, quick and effective manner, gives place to judges who have not a judicial notion in other law systems. In Turkish literature, it is rightly emphasized that such an application is not appropriate for Turkish law. TCC Art. 5A is also examined within frame of civil procedure and commercial law. Within civil procedure law frame, the concept of cause of action is examined, as well as features of TCC Art 5A in relation to claim in actions. Within commercial law frame, since the agreement concluded within mediation is a contract in context of substantial law, the notion of prudent merchant is evaluated. Furtermore, for mandatory mediation demonstrates features within light of Code of Mediation Art. 5 and principal of confidentiality, an evaluation of trade secrets are also conducted. The third and last chapter concentrates on examination of mediation as a cause of action in equity company disputes. Thus, an action named shareholders' action in German law, which is clarified using notion of actio pro socio, is evaluated. According to this evaluation it is concluded that, unlike simple partnerships, shareholders shall submit their claims against legal entity of equity companies and not against other shareholders. Neverthless, it is also observed that in some cases shareholders are entitled to submit the tools of defence of equity companies for interests of company. This evaluation is essential in order to determine the parties of dispute and the persons effected from the agreement reached at the end of mandatory mediation process. Following this evaluation, the kinds of disputes in equity companies, which fall into scope of TCC Art. 5A, are determined and the features demonstrated by them in context of mediation as a cause of action are defined. In order to comply with this evaluation, information on each subject of action is given, features of the relevant actions are explained and in the light of all evaluations, conditions of application of mediation as a cause of action are explained. Finally, in light of evaluations made within this study, our de lege ferenda opinions on mandatory mediation in equity companies are set. Within this frame, since dispute in equity companies are subject to limitations on equity company law and compulsory legal rules, it is stated that they might not always compatible with mediation as a cause of action. In addition, possible problems arisen from lack of legal supervision in mediation process are also mentioned. As a result, it is concluded that, it would be more convenient to regulate court annexed dispute resolution tools, similar with examples of Germany and Switzerland. With regard to bankruptcy proceedings, it is concluded that possible problems in relation to Turkish Code of Bankruptcy and Enforcement Art. 226 are highlighted and it is suggested that, in order to eliminate such problems, necesarry regulations by legislator should be made. Lastly, taking the goals of mediation into consideration, in order to reach these goals effectively, the importance of giving parties the opportunity to be able to choose other means of dispute resolution apart from mandatory mediation, is found to be essential. Thus, dispute resolution process will take place in a quick and cheap manner and parties will have the chance to be able to choose a dispute resolution method that suits their needs and interests.
Keywords: MARD; Mediación; Mediation; Mediação; Médiation

Milletlerarası ticari tahkimde hakem kararlarının iptali - Ersari̇, Danyal (Marmara Üniversitesi, 2023)
Günümüzde ticaretin globalleşmesi ile birlikte tahkim, uluslararası uyuşmazlıkların çözümünde devlet mahkemelerine nazaran kişiler, şirketler ve devletler tarafından daha çok tercih edilir hale gelmiştir. Bu tercihin en önemli sebeplerinden biri tahkim yargılaması sonucunda verilen hakem kararlarının tıpkı mahkeme kararlarında olduğu gibi kesin ve bağlayıcı olmasıdır. Ancak aleyhine karar verilen taraf, ilgili hakem kararının adalete uygun olmadığını düşünebilir. Bu bağlamda hakem kararlarının devlet mahkemeleri tarafından denetlenebilmesi için neredeyse tüm milli hukuk sistemlerinde hakem kararlarına karşı denetim yolu olarak "iptal davası" öngörülmüştür. İptal talebinde bulunan taraf belirli sebeplerin olması halinde tahkim yeri mahkemesinde iptal davası açabilecektir. Hakem kararına karşı iptal talebinde bulunan tarafın amacı, kararın bir kısmını ya da tamamını geçersiz hale getirmek ve icrasını engellemektir. UNCITRAL Model Kanun ve ulusal hukuk sistemlerinde iptal sebepleri sınırlı şekilde sayılmıştır. Ancak bazen bu iptal sebeplerinin faklı şekillerde yorumlandığı görülmüştür. İptal sebeplerinin geniş yorumlanması hakem kararlarının iptal olasılığını orantısız şekilde arttıracaktır. Bu durum alternatif uyuşmazlık çözüm yolu olan tahkimin güvenirliğine zarar verdiği gibi uzun, meşakkatli ve masraflı tahkim yargılama sürecini de boşa çıkaracaktır. Ancak, iptal sebeplerin adaletsizliğe yol açacak şekilde çok dar yorumlanması da keyfiliğe, tutarsızlığa ve tarafların istemediği sonuçlara yol açacaktır. Bu çerçevede Türk kanunları dahil çeşitli ülkelerdeki kanunları ve mahkeme uygulamalarını dikkate alarak kanımızca iptal sebepleri bakımından doğru yaklaşımları ortaya koymaya çalışacağız. Çalışmamız üç bölümden oluşmaktadır. İlk bölümde milletlerarası tahkime ilişkin genel bilgiler, yabancı hakem kararlarının tabiiyetinin belirlenmesi ve iptal davasına konu olabilecek yabancı hakem kararlarının türleri yer almaktadır. Bunun devamında, ikinci bölümde, çeşitli ülkelerin tahkime ilişkin kanunları, tahkime ilişkin milletlerarası literatürde kabul gören hukuki metinleri de dikkate alınarak iptal sebepleri ortaya konulacaktır. Aynı zamanda, konu ile ilgili doktrindeki görüşlere yer verilerek çeşitli ülkelerde verilen mahkeme kararları çerçevesinde iptal sebeplerine ilişkin yaklaşımlara ver verilecektir. Çalışmamızın üçüncü ve son bölümünde ise iptal davasının tarafları, iptal davasında görevli ve yetkili mahkeme ve iptal davasından feragat konuları Türk hukuku ve karşılaştırmalı hukuk bakımından incelenmeye çalışılmaktadır. Along with the globalization of trade, arbitration has become more preferred by individuals, companies and states than state courts in resolving international disputes. One of the most important reasons for this preference is that the arbitral awards given after the arbitration proceedings are final and binding, just as the court decisions. However, the party rendered against the award may consider it unjust. In this context, in order for the arbitral awards to be audited by the state courts, "annulment case" is designed as a legal remedy in almost all national legal systems. The party requesting annulment may file an action for annulment in the court of the place of arbitration if there are certain reasons. The purpose of the party requesting annulment against the arbitral award is to invalidate some or all of the decision and to prevent its execution. Although the reasons for annulment are limited and similar in many legal systems, the interpretation of these reasons is of great importance. A broad interpretation of the grounds for annulment will disproportionately increase the possibility of annulment of arbitral awards. This situation will not only harm the reliability of arbitration, which is an alternative dispute resolution method, but will also nullify the long, laboursome and costly arbitration proceedings. On the other hand, much narrower interpretation of the grounds for annulment in a way that leads to injustice may lead to arbitrariness and inconsistency, as well as result in undesirable results by the parties. Considering these, we will try to put forward approaches that can be consistent in terms of the grounds for annulment, taking into account the laws and court practices in various countries, including Turkish laws. This study consists of three parts. In the first part, general information about international arbitration, determination of the nationality of foreign arbitral awards and types of foreign arbitral awards that may be subject to annulment proceedings are included. Following this, in the second part, the reasons for annulment will be presented considering the arbitration laws of various countries and the internationally accepted legal texts on arbitration. At the same time, we try to put forward the approaches regarding the reasons for annulment within the framework of the court decisions given in various countries by giving place to the opinions in the doctrine on the subject. In the third and final part of our study, the parties of the annulment case, the competent court in charge of the annulment case and the waiver of the annulment case are to be examined in terms of Turkish law and comparative law.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitral Awards; Arbitration; International commercial arbitration

Bireysel iş hukukunda arabuluculuk - Gül Küçükkaya, Hande (Marmara Üniversitesi, 2023)
Arabuluculuk tarafların tarafsız bir üçüncü bir kişinin yardımı ile ihtilaflarını çözmeye yardımcı olması olarak tanımlanabilir. Türkiye'de özel hukuktan doğan ve tarafların üzerinde serbestçe tasarruf edebilecekleri uyuşmazlıkların arabuluculuk ile çözümüne ilişkin 6325 sayılı Hukuk Uyuşmazlıklarında Arabuluculuk Kanunu'nun 2013 yılında kabulü ile arabuluculuk uygulamasına geçilmiştir. 7036 sayılı İş Mahkemeleri Kanunu ile 2018 yılı itibariyle dava şartı arabuluculuk kavramı Türk hukuk literatürüne girmiştir. 7036 sayılı İş Mahkemeleri Kanunu md.3 uyarınca kanuna, bireysel iş sözleşmesine, toplu iş sözleşmesine dayanan alacak, tazminat veya işe iade talebi ile açılan davalarda arabuluculuğa başvurulması dava şartıdır. İtalya, Almanya ve ABD'nin bazı eyaletlerinde iş hukukunda dava şartı arabuluculuk uygulaması yoktur. İngiltere'de iş mahkemelerine başvurmak için önce ACAS isimli kuruma başvurmak gerekir. ABD 'de ise iş ilişkilerindeki ayrımcılık iddiaları öncelikle EEOC'de görülmektedir. Bireysel İş Hukukunda Arabuluculuk başlıklı doktora tezi çalışmamız dört bölümden oluşmaktadır. Çalışmanın birinci bölümünde alternatif uyuşmazlık çözüm yöntemleri kavramı ve belli başlı alternatif uyuşmazlık yöntemleri irdelenerek incelenmiş, ikinci bölümde arabuluculuk kurumu, amacı, prensipleri, türleri, arabulucunun hak ve yükümlülükleri, arabulucu ve arabuluculuk sözleşmelerinin hukuki mahiyeti ve arabuluculuk etiği gibi konular çalışılmıştır. Mukayeseli İş Hukukunda Arabuluculuk başlıklı üçüncü bölümde, arabuluculuğun anavatanı olan Amerika Birleşik Devletleri, Birleşik Krallık gibi Anglo Sakson sistemindeki devletlerde, İtalya, Almanya, Fransa gibi Roma Cermen sistemindeki devletlerde ve Avrupa Birliği müktesabatında arabuluculuğun nasıl düzenlendiği ve son olarak dördüncü bölüm olan Türk İş Hukukunda Arabuluculuk başlığı altında, dava şartı arabuluculuk kavramına ilişkin konular yargı kararları da işlenerek ayrıntılı olarak irdelenmiştir. Mediation can be defined as helping parties resolve their disputes with the help of a third party. With the adoption of the Law No. 6325 on Mediation in Civil Disputes in 2013, mediation has been implemented regarding the resolution of disputes arising from private law and on which the parties can freely dispose of. As of 2018, with the adoption of the Labor Courts Law numbered 7036 the concept of mediation as a cause of action in employment disputes litigation introduced in our legal literature. Pursuant to Article 3 of Labor Courts Law numbered 7036, lawsuits filed with the demand for receivables, compensation or reemployment based on the law, individual employment contract, collective bargaining agreement are subject to mediation as a cause of action. In Italy and Germany mediation in employment disputes does not exist. In England, in order to apply to the labor courts, firstly it must be applied to ACAS. In the United States of America, for discriminatory allegations in the employment relation firstly EEOC must be addressed. The doctoral thesis titled Mediation in Individual Employment Law consists of four parts. In the first part of the study, the concept of the alternative dispute resolution methods is investigated by examining the main alternative dispute methods, in the second part, the mediation institution, its purpose, principles, types, rights and responsibilities of the mediator, the legal nature of the mediator and mediation agreemets and mediation ethics are studied. In the third part titled Mediation in Comparative Employment Law, the Anglo-Saxon countries such as the United States of America and the United Kingdom, which are the homeland of mediation, in the Roman Germanic system states such as Italy, Germany France and in European Union legal system are explained and lastly under the title of Mediation in Turkish Employment Law, which is the fourth part, the issues related to the concept of mediation as a cause of action are also discussed in detail adding judicial decisions.
Keywords: ACAS; Arabuluculuk; Cause of action; Comparative law; Danışma; Dava şartı; Karşılaştırmalı hukuk; Labour disagrement; Labour dispute; Labour law; Mediation; Uzlaşma ve Tahkim Servisi; İş hukuku; İş uyuşmazlıkları

Milletlerarası ticari tahkimde delillerin değerlendirilmesi - Kesi̇kli̇, Ömer (Galatasaray Üniversitesi, 2023)
It is nowadays generally accepted that international commercial arbitration is the most popular method of resolving international disputes between commercial parties. This popularity is the cumulative result of many advantages that international commercial arbitration offers to the parties. It is suggested in the literature that one of these advantages is the freedom of parties and the resulting procedural flexibility. In virtue of this principle, the parties have the opportunity to establish a specific method of adjudication adapted to the nature of their dispute. This opportunity is provided by the fact that the arbitration regulations do not include detailed rules on the collection of evidence, thus leaving the parties and the arbitrators' range of motion. Therefore, we consider that this procedural flexibility has emerged as a possibility obtained at the expense of certainty in international commercial arbitration proceedings. This uncertainty is to such an extent that it also warrants the question as to whether there is an applicable law to take evidence in international commercial arbitration proceedings. Such procedural flexibility afforded to the parties, however, comes at a price of uncertainty with respect to arbitral procedure. International commercial arbitration developed as a reaction to the failings of proceedings in domestic courts, which were subject to detailed rules of evidence. Thus, the consensus in the arbitration community is that party freedom and the procedural flexibility that comes with it are fundamental attributes of arbitration. Although this presumption is theoretically correct; in other words, the parties are indeed able to craft such a procedure that would perfectly fit for adjudication of their disputes, mostly it does not reflect the practical reality. In practice, when parties are negotiating the terms of an agreement to govern their business relationship, they generally tend to avoid discussions as to what will happen if things go wrong. As a matter of fact, according to our practice experiences, when one of the parties' legal counsel tries to address such hypothetical scenarios, the parties generally prefer to suppress such "negative thoughts" and refuse to make in-depth discussions as to how a possible dispute is to be handled. Hereby, this leaves open the question of the procedure to be followed in arbitration proceedings in case of potential disputes. As a result, the provisions on how to resolve disputes that may arise between the parties, in other words, the "dispute resolution" provisions, are left to the very end of the negotiations and passed over in a few sentences. When the relationship between the parties becomes truly strained and a dispute comes to an unavoidable stage, it becomes even less likely that the parties will agree on how to gather evidence on the dispute in question. In a such situation, any suggestions made by one party regarding the procedure for the taking of evidence will be viewed with suspicion by the other party. In an environment of suspicion and animosity, it is often unrealistic to expect productive negotiations to take place on procedural matters. As a result, although the parties have a wide range of motions to make agreements regarding the method of collecting evidence in arbitration proceedings, they are often unable to exercise this authority in practice. As the parties are not exercising their rule-making powers, this important task, which is decisive for the resolution of the dispute, shifts to the arbitrators. Therefore, in our opinion, it would not be a wrong assessment to say that the freedom of the parties has turned into the freedom of the arbitrator in practice. Once appointed, arbitrators have to decide on many issues with respect to the taking of evidence as rules applicable to arbitration are generally silent as to these matters. Although arbitrators have the opportunity to be guided by some non-binding rules, such as the IBA Rules and the Prague Rules, which are considered to be effective and instructive in the arbitration community, they are ultimately left to make their assessments and reach an award based on their judgment. The above-mentioned non-binding rules can undoubtedly assist arbitral tribunals to a certain extent with regard to the taking of evidence. However, it is not possible to say that these rules are enforceable guidelines that can be blindly followed by arbitral tribunals. A closer look at these rules reveals that they leave many issues to the discretion of the arbitral tribunals. Of course, any decision regarding the taking of evidence in international commercial arbitration is already within the discretion of the arbitral tribunals, even in the absence of these rules. Therefore, these provisions, which have been drafted to allow the arbitral tribunals to decide as they see fit, are no more than general guidance on how to exercise their discretion. For these reasons, even if the parties have agreed on the application of these non-binding rules, the fact remains that the collection and evaluation of evidence are still left to the discretion of the arbitral tribunals. This study takes an inductive approach by analyzing the normative and non-binding rules of law applicable to evidence in international commercial arbitration. Firstly, this study examines whether there is a body of rules that can be characterized as the law of evidence in international commercial arbitration. It is determined that there is a law of evidence in international commercial arbitration; however, its content is rather composed of general principles. After determining that these rules have normative value, it is examined how and to what extent these general principles are concretized in terms of the types of evidence used in international commercial arbitration. Although the degree of concretization of these principles varies according to the types of evidence, as a general characteristic, it is determined that arbitral tribunals are left with a very wide discretionary power. It is concluded that arbitral tribunals have a wide latitude of action with respect to the submission of documents, the presentation of witness testimony, the use of expert testimony, the use of discovery and the extent of the res judicata effect of a prior award. Subsequently, the rules on the admissibility and evaluation of evidence are analyzed and it is concluded that the arbitral tribunals have wide discretion in international commercial arbitration, as in other matters relating to evidence and even the discretion regarding the evaluation of evidence is relatively wider. Since it is difficult to review the discretionary power exercised in these matters, it is observed that the arbitral tribunals' decisions on evidentiary issues fall outside the scope of judicial review. This leads to a further blurring of the already grey evidentiary issues in international commercial arbitration proceedings. This is because it is not possible to determine the extent to which the arbitral tribunal has relied on evidence that ostensibly played a role during the proceedings. In the last instance, although the arbitrators' discretionary powers are limited by general principles such as due process and opportunity to be heard, the limits of such discretionary powers are, generally speaking, somewhat blurred as these are general principles. Another issue is that arbitral tribunals are often subject to pressure from the parties when making their decisions on the taking of evidence during the arbitral proceedings. The parties are more interested in being the winner of the concrete proceedings than in the proper conduct of the proceedings in accordance with the law, procedure and rules. In this sense, a party whose request for evidence is likely to be rejected will often argue that the arbitral tribunal's decision violates the principle of a fair trial, even if this is not the case. It is in these circumstances that arbitral tribunals must strike a balance between a fair trial and an efficient trial and make appropriate decisions on evidentiary issues. If arbitral tribunals emphasize procedural efficiency and defer to the parties' presentation of their claims and defences, this may not in itself constitute an obstacle to legally correct decisions. However, this would violate the fundamental procedural safeguards of the participants in the proceedings and may even lead to arbitration proceedings becoming a mechanism for arbitrary and haphazard decision-making. If the opposite approach is taken, in other words, if the priority is to uncover the material truth at all costs and the procedural economy is put on the back burner, this will result in costly and protracted proceedings that will far exceed the limits of reasonableness. Given the limited scope of the guidelines available to arbitrators on the collection and evaluation of evidence, striking this balance is not an easy task. Therefore, it is quite understandable that arbitral tribunals, when deciding on evidentiary issues, may prefer the safer route and give precedence to claims of breach of the principle of a fair trial, even at the expense of the efficiency of the proceedings. Additionally, the confidential nature of the international commercial arbitral proceedings also amplifies the problem. As a result of this principle, the available knowledge as to the practice of arbitration becomes limited to anecdotal stories as to what has happened in certain individual international commercial arbitration proceedings. The arbitrators do not have sufficient opportunity to know about how their colleagues have dealt with certain issues that may have similarities with the issues that they have been trying to solve. In conclusion, in light of the foregoing, since the arbitral tribunals are the rule-makers of arbitration proceedings, the extent to which arbitration proceedings will function correctly and efficiently depends on the experience of the arbitral tribunals and their knowledge of the law, procedure and rules. Basing a correct and efficient arbitration procedure solely on the initiative of experienced arbitrators reduces the 'certainty' of the arbitral procedure. In the face of this situation, it may be tempting to argue that it is inappropriate for arbitrators to have so much freedom and that the rules applicable to arbitral proceedings should be revised to be more detailed. Indeed, there are those who argue that such a change should take place. In the final analysis, a good system should be able to function well regardless of how qualified (or unqualified) its participants are. It is obvious that an argument that sees detailed procedural rules as a remedy for this would contradict the historical development of arbitration and therefore would not be accepted by the international arbitration community. Likewise, from the other side of the coin, it could be argued that detailed procedural rules that are not appropriate to the nature of the individual dispute would prevent qualified and experienced arbitral tribunals from formulating rules that are appropriate to the resolution of the dispute in question, and that the hands of arbitral tribunals may be tied in this way. Although it may be argued that these counter-arguments are equally justified, they do not negate the fact that certainty should be ensured in international commercial arbitration proceedings. Therefore, this suggests that it may be appropriate to resort to alternative methods to ensure certainty. Indeed, it would be a mistake to assume that the only way to achieve certainty is through a detailed set of rules, as we, as legal practitioners in the Continental European legal system, are accustomed to. In the countries subject to the Common Law system, many branches of law do not have such a detailed set of rules and therefore it is not possible to claim that these legal systems lack certainty. Especially in the common law, certainty is provided by case law. If the same logic were to be applied to international commercial arbitration proceedings, it would mean that making information on arbitration proceedings more accessible could help to achieve the goal of certainty. In recent years, there have been some initiatives recognizing the benefits of this approach. While arbitral tribunals are under no obligation to follow the decisions of other arbitral tribunals, having the opportunity to see that there is a consistent pattern of decisions on a particular issue would undoubtedly provide valuable guidance for arbitral tribunals. As the pool of information available to arbitral tribunals and the parties expands, it is obvious that the grey areas regarding evidence in international commercial arbitration will diminish over time. In this way, it will be possible to achieve greater certainty without undermining the fundamental values of the arbitral procedure. Reducing the uncertainty caused by procedural flexibility on procedural certainty in this way will contribute significantly to the development of international commercial arbitration.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Delil; Evidence; International Arbitiation Law; Milletlerarası Tahkim Kanunu; Proof (presentation); Tahkim; İbraz (İspat)

Ticari davalarda arabuluculuk - Yildirimoğlu, Hakan (İstanbul Ticaret Üniversitesi, 2023)
Dünya genelinde, uyuşmazlıkların mahkeme dışında alternatif uyuşmazlık çözüm yolları ile çözülmesi konusunda artan bir eğilim bulunmaktadır. Alternatif uyuşmazlık çözüm yollarından biri de arabuluculuktur. Arabuluculuk gönüllülük esasına dayanan bir uyuşmazlık çözme biçimidir. Arabuluculuk sistemi, AB'ye üye bazı ülkeler başta olmak üzere birçok ülkede özellikle ticari uyuşmazlıklarda uygulanmakta ve sonuçları itibariyle tarafları memnun etmekte, yargının yükünün de ciddi şekilde azaltılmasına destek olmaktadır. Yargının iş yükünün hızla arttığı, yargılamadaki gecikmeler nedeniyle adalete duyulan güvenin azaldığı bir ortamda arabuluculuk uygulamaları birçok ülkeye örnek olmaktadır. Ülkemizde de arabuluculuk uygulanmaya başlanmış; hatta en sık karşılaşılan uyuşmazlıklardan iş uyuşmazlıkları, ticari uyuşmazlıklar ve tüketici uyuşmazlıkları dava şartı arabuluculuk kapsamına alınmıştır. Ticari davaların zorunlu arabuluculuk yoluyla çözülmesi uygulamada bazı sorunlara ve çelişkili yargı kararlarının ortaya çıkmasına neden olmuştur. Arabuluculuk, Ticari Davalar, Ticari Davalarda Arabuluculuk, Avrupa Birliği, Zorunlu Arabuluculuk, Alternatif Uyuşmazlık Çözüm Yolları, Dava Şartı Arabuluculuk, Uzlaşma. There is an increasing trend around the world related with the resolution of disputes through alternative dispute resolution methods out of court. One of the alternative dispute resolution methods' is mediation. Mediation is a form of dispute resolution on a voluntary basis. The mediation system is applied especially in commercial disputes in many countries, also in some member countries of European Union. The mediation not only satisfies the parties in terms of its results but also helps to reduce the burden of the judiciary. In a world where the workload of the judiciary increases rapidly and trust in justice decreases due to delays in the trial, commercial mediation practices in European countries set an example for many other countries. Mediation is not also practised in Turkiye but also mandatory in labor disputes, commercial disputes and consumer disputes. Contradiction and discrepancy between the court decisions and other judicial problems arised arised as a result of mandatory mediation. Mediation, Commercial Disputes, Mediation in Commercial Disputes, European Union, Mandatory Mediation, Alternative Dispute Resolution, Condition of Litigation, Commercial Mediation. Reconciliation, Voluntary Mediation
Keywords: Alternate dispute; Alternatif uyuşmazlık; Arabuluculuk; Avrupa Birliği; Commercial cases; Commercial disputes; European Union; Hukuk düzeni; Incompatibility; Judicial decisions; Law order; Mandatory mediation; Mediation; Ticari davalar; Ticari uyuşmazlıklar; Uyuşmazlık; Yargı kararları; Zorunlu arabuluculuk

İslam borçlar hukuku açısından ticari ihtilafların çözümünde 'Arabuluculuk' - Almasri, Raed (Ankara Üniversitesi, 2022)
Bu tez, anlaşmazlıkları çözmede arabuluculuk konusunu ele almaktadır. Arabuluculuk konusu ticari mali muamelelerdeki anlaşmazlıklar ile sınırlıdır. Dolayısıyla tez ailevi anlaşmazlıklardaki nafaka gibi diğer mali anlaşmazlıklara değinmemektedir. Tez konusu fıkhi açıdan ele alındığı için, dört fıkhi mezhebin konuyla ilgili görüşleri, mukayeseli olarak işlenmiş, mezhepler arasında ihtilaf ve ittifak edilen noktalar ele alınmış ve görüşler arasında tercih yapılarak ortaya konulmuştur. Tez; bir mukaddime, üç bölüm, bir sonuç ve kaynakçadan meydana gelmektedir. Mukaddime de tezin planı, fihrist ve içerik ele alınmıştır. Tezin birinci bölümünde; arabuluculuk kavramının tanımı ve meşruiyeti, ikinci bölümde; arabuluculuğun rükünleri ve arabuluculukla ilgili hükümler ve şartlar, üçüncü bölümde ise; arabuluculuğun sonuçları ve etkisi ele alınmıştır. The dissertation aims to cover the subject of mediation in dispute resolutions exclusively in commercial disputes. Therefore, the research does not cover mediation in other disputes such as domestic disputes even when it's related to financial matters such as alimony. The research also studies mediation in commercial disputes from a jurisprudential perspective. Hence the jurists' opinions are presented and analyzed in a comparative approach to show its similarities, differences and present a jurisprudential preference. The dissertation is presented in an introduction, three chapters, a conclusion followed by the list of references and resources. The introduction provides an insight into the research contents and methodology. The first chapter discuss the definition of mediations and its legitimacy. The second chapter tackle the main pillars of mediations and clarify its ruling and conditions. Finally, the third chapter view the results of mediations and its expected impacts.
Keywords: Arabuluculuk; Borçlar hukuku; Commercial disputes; Incompatibility; Islamic law; Law of obligations; Mediation; Ticari uyuşmazlıklar; Uyuşmazlık; İslam hukuku

Yönetim kurulu krizleri ve çözüm yolları - Meti̇n, Umut (Kadir Has Üniversitesi, 2021)
YK farklı sorunlar veya uyuşmazlıklarla yüzyüze gelebilir. Sorunlar veya uyuşmazlıklar kriz halini alarak YK'nın işleyişine olumsuz etki edebilmektedir. Kriz derinleştikçe, YK işlevini yerine getirmekte zorlanabilir. Krizin bir adım ötesinde ise YK kilitlenebilmektedir. Pay sahipleri arasındaki menfaat çatışmaları, YK kriz ve/veya kilitlenmesinin en sık rastlanan temel nedenidir. Kilitlenme durumunda, YK toplantı yapamamakta veya karar alamamaktadır. Oysa ki, YK her daim çalışabilmesi gereken bir organdır. YK'nın kilitlenmesi, şirketin de kilitlenmesi sonucu doğurabilir. Bu durum öyle risklidir ki, şirketin feshi/tasfiyesi yakın bir ihtimal olabilmektedir. Bu aşamada kilidin olabildiğince hızlı açılması şirketten menfaati olan herkes için (pay sahipleri, YK üyeleri, çalışanlar, alacaklılar, kamu vb.) hayati önemdedir. Bu nedenle, şirket esas sözleşmesinde YK kriz ve kilitlenmelerine karşı önlemler planlanmalıdır. Tek kişiden ibaret YK modeli ve YK'ya danışma kurulu desteği kilitleme riskine karşı önerdiğimiz modeldir. Pay sahipleri sözleşmesi, aile şirketleri için aile anayasası gibi hukuki metinler kriz ve/veya kilitlenmeye ilişkin tedbirler içermelidir. Önlemlere, rağmen kilitlenme gerçekleşir ise, öncelikle YK içi ve şirket içi çözümler uygulamaya konulmalıdır. Bu tür yöntemler yeterli olmazsa, AUÇY'nin tatbiki, şirket dışından gelen çözümün ilk aşaması olarak kabul edilmelidir. Arabuluculuk ile YK kriz ve kilitlenmelerine karşı etkin, hızlı ve kalıcı çözümler sağlanabilmektedir. "Med-arb" veya "Arb-med" gibi yöntemlerden de faydalanılabilir. Tahkim de bir çözüm yoludur. Bu yolda "seri tahkim usulü" YK kilitlenmeleri için daha uygundur. Son çare olarak nitelediğimiz, dava yolu ise, bazı durumlarda içinde şirketin fesih ve tasfiye riskini barındırdığı için kilidi açmak ve hatta kilidi kırmak için uygulamaya konulabilir. Mahkemelerde, organ yokluğuna dayalı fesih davası ve özellikle haklı sebeple şirketin feshi davası çözüm sağlayabilecek dava tipleridir. Özellikle, haklı sebeple şirketin feshi davası, kriz ve kilitlenmelere daha uygun olup, stratejik sonuçlara da imkân vermektedir. Bunlar yanında, YK işleyişinde yapay zekâdan faydalanmanın mümkün olup olmadığı, yapay zekâya YK üyesi olarak kişi statüsü verilip verilemeyeceği, bu meselenin YK üyelerinin sorumluluğuna etkisi incelenmiştir. Board of Directors may face various disputes or disagreements. These disputes or disagreements may turn into crises which negatively affect the normal functioning of the board. As the crisis deepens, Board of Directors could have difficulties in fulfilling its function. Moreover, a step further from the crisis, Board of Directors might even be locked up. Conflicts of interest among shareholders are known as the most common cause of the board of directors crisis and/or deadlock. In event of a deadlock, Board of Directors, a body should always be able to function, cannot hold meetings or make decisions anymore. The deadlock of board of directors, may lead the entire company to be locked down whereas the company may encounter the possibility of dissolution and liquidation. At this point, unlocking the crisis as quickly as possible is vital for relevant competent persons of the company. Therefore, measures should be taken in the company's articles of association against Board of Director crisis and/or deadlock. One-person Board of Directors model and support of Advisory Board to Board of Directors is the model we recommend against the risk of locking. Legal texts such as shareholder agreements and family constitutions for family companies should include measures regarding deadlock. If a deadlock has occurred in spite of precautions, first of all, Board of Directors and internal remedies should be implemented. If such methods are not sufficient enough, Alternative Dispute Resolution (ADR) methods should be regarded as the first stage of external intervention. Effective and rapid solutions can be achieved against deadlocks via mediation. "Med-arb" or "Arb-med" could be also utilised. Arbitration is also a way and in this way; "expedited (fast-track) arbitration" procedure is more suitable for corporate deadlocks. Litigation, as the last possibility that we propose, could also be applied to unlock or even break the lock, since it contains the risk of dissolution and liquidation of company in some cases. In courts, termination action based on the absence of organs and especially termination of the company with a valid reason are the types of cases that may provide a solution. Especially termination of the company with a valid reason is more suitable for crisis and deadlocks, and also grants strategic results. In addition to these, it has been questioned in this study whether Board of directors possibly benefit from artificial intelligence in the operations and whether AI can be attributed a person-status as a member of Board of Directors. The effects of this issue on the responsibility of the members of Board of Directors have been analysed.
Keywords: Absence of body; Arabuluculuk; Arbitration; Artificial Intelligence; Board directors; Conseil d'administration; Crisis; Deadlock; Inteligência artificial; Intelligence Artificielle; Kilitlenme; Kriz; Mediation; Members of the board directors; Médiation; Organ yokluğu; Tahkim; Yapay zeka; Yönetim kurulu; Yönetim kurulu üyeleri

Milletlerarası ticari tahkimde usule ilişkin konularda irade serbestisi - Takavut, İbrahim Doğan (İstanbul Üniversitesi, 2020)
Party autonomy is a well-accepted doctrine codified by national, international and supranational organizations that enables parties to be able to not only shape their contract but also their dispute resolution methods. It is believed that parties know their best interests; therefore, it is reasonable to give parties the freedom to decide whom they contract with and on what terms. This maximizes the autonomous freedom of the parties. Therefore, today it is well accepted that parties could waive their right to go to court and choose arbitration instead. However, through history, party autonomy has been seen as a direct threat to sovereign authority. States were always suspicious that arbitration hearings may not be as fair as court hearings since parties have the right to manipulate the arbitration processes. As a direct result of this, states regulated restrictions on party autonomy in international commercial arbitrations. Unfortunately, there is not an accepted definition of these restrictions and their effects on party autonomy have not been established or regulated internationally. Since party autonomy is the backbone of international commercial arbitration, it is important to crystalize the restrictions on party autonomy in procedural issues which directly affects the wellbeing of the arbitration process. Well accepted international regulations such as the New York Convention on Recognition and Enforcement of Foreign Arbitral Awards or UNCITRAL Model Law on International Commercial Arbitration helped to establish a unified system of restrictions on party autonomy but every state and state's courts interpret these restrictions differently. As procedural issues affect the result of international commercial arbitration, restrictions on party autonomy in procedural issues should be examined carefully. It is not an exaggeration that in international commercial arbitration the real and complicated questions most of the time originate from the issues of the boundaries of party autonomy. The tension between the party autonomy and efficiency of an arbitration process affects every decision which can be made by parties, arbitrators or courts. Therefore, this dissertation will investigate these problems in three parts by outlining; the source of party autonomy, the restrictions of party autonomy and the applications of these restrictions to party autonomy in procedural issues in international commercial arbitration. In the first part, the origin of party autonomy doctrine and how the doctrine developed throughout time will be examined. The law of arbitration, lex arbitri will be examined first. There are two accepted theories to determine lex arbitri. According to the territorialism theory, arbitration gets its power from the law of the place where the arbitration takes place. This theory suggests that the place where the arbitration takes place has control power over the procedure of arbitration. On the other hand, delocalization theory suggests that arbitral tribunals are detached from and not under the control of the law of the seat of arbitration. Although it looks like delocalization theory suits the needs of the international trade practice better because it assumes that arbitration is not in control of any law, it is still important to accept the power of the seat of arbitration since arbitration always needs a law to be controlled and get help. This section will also cover how different countries and international regulations determine lex arbitri and how it is determined in Turkish law according to the Turkish International Arbitration Law, Law no.4686. In the second part, restrictive measures of party autonomy will be examined. It will start with why party autonomy in procedural issues is needed to be restricted. Then the source of these restrictions will be mentioned. Afterwards, the common notions of the restrictions will be examined under the concepts of principles and rules. Under principles, the public policy and the common due process issues such as party equality, right to be heard, independence and impartiality of arbitrators will be examined in great detail. Then, mandatory rules which are based on these principles and their effect on party autonomy will be explained. The section will be closed with the examination of the circumstances where these principles and rules contradict each other. The main purpose of the second part is to look for commonly accepted problems of restrictions of party autonomy in procedural issues and how these common problems may evolve to a uniformed standard of the law, namely lex proceduralia. In the third part, the application of restrictions on party autonomy will be examined. The application of restrictions has different effects on parties, arbitrators and courts. Parties' autonomy is restricted while they are preparing their agreement on procedural issues, arbitrators are restricted during the arbitration processes and courts are restricted while helping the arbitration or controlling the awards. Before the arbitration process is initiated, parties' autonomy to shape their agreement looks like it is almost unlimited. However, parties' autonomy is always restricted by their choices. This situation is called the autonomy paradox. Therefore, the question of what parties can decide before the arbitrators join the processes is of the upmost importance. When the process starts and arbitrators start working, they balance the choice of parties and the restrictions of party autonomy. Since it is accepted that arbitrators are bound by the parties' choice and their power comes from the agreement of parties, it should be questioned whether they need to execute every choice of parties even if the choice is against mandatory provisions of lex arbitri or general accepted due process norms. Last but not least, courts' role on determining the party autonomy will be questioned. The power of courts to intervene in the arbitral process determine the practical limits of the autonomy of parties. During the arbitration process, the court may intervene in the process to help or control the arbitration; but real control power comes from when one of the parties asks courts to set aside or enforce the arbitral awards. While courts examine the arbitral awards, they also indirectly decide the limits of party autonomy. Therefore, this section will examine, which restrictions will affect the fate of the arbitral awards and how the courts should evaluate these restrictions. In conclusion, the dissertation will mainly investigate the topic of freedom of parties to determine the procedural issues in international commercial arbitration. It will aim to interpret and make use of the party autonomy doctrine as coherent as it can in the modern age. By illustrating the definition and limitations of the party autonomy in the procedural issues in international commercial arbitration, the dissertation will try to find a common international ground. This common ground may help to keep arbitration processes efficient while it provides fair hearings.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration boards; Commercial Arbitration; Commercial law; Free will; Hakem usulu; International Arbitiation Law; International Chamber of Commerce; Milletlerarası Tahkim Kanunu; Party autonomy; Procedural law; Tahkim; Tahkim kurulları; Ticaret hukuku; Uluslararası Ticaret Odası; Usul hukuku; Özgür istenç; İrade muhtariyeti